Protecting Indigenous Rights in the Indonesia–Papua New Guinea Border Area - Kalalo, Julianto Jover Jotam; Silambi, Erni Dwita; Maturbongs, Edoardus E; Marpaung, Dewi Natalia (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The determination of customary land rights for indigenous communities in border areas grows increasingly complex when assessing individual claims within the framework of collective rights. This study aims to formulate a legal protection model for the customary land rights of indigenous communities along the Indonesia-Papua New Guinea border. To formulate this model, the research will comparatively analyze the conceptual frameworks governing customary rights across three existing border areas, namely in Jayapura Regency, Boven Digoel Regency, and Merauke Regency. The research method used is normative empirical, with data collection techniques through observation, documentation, and interviews. The data analysis technique used in this legal research is qualitative-descriptive data analysis. Critical Review of previous studies reveals a significant research gap regarding the protections for customary law communities, especially customary land rights in the Papua border area. This study identifies the absence of a comprehensive scholarly examination regarding the protection and control of customary land rights in the border area between Indonesia and Papua New Guinea, especially in Merauke Regency, Boven Digoel Regency, and Jayapura Regency.